PENGARUH CITRA MEREK, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN Studi Pada Pelanggan Datsun di PT. Indomobil Trada Nasional Cabang Kebon Jeruk - Lucy Nancy Simatupang (Jurnal Manajemen, 2017)
The purpose of this study to analyze the effect of Brand Image, Product Quality and Service Quality on Customers Satisfaction. The population in this study are all customers Datsun in PT. Indomobil Trada Nasional Kebon Jeruk unknown number. Total sample of 60 people with the method of Non-Probability sampling with Accidental Sampling technique.The method of collecting data using a survey questionnaire. Analysis of data using multiple linear regression with SPSS 22. The results showed that the partial t test known brand image variable has significant effect on customers satisfaction, product quality variable did not significantly effect on customers satisfaction and service quality variable has significantly effect on customers satisfaction. Based on F test found that the variable Brand Image, Product Quality and Service Quality simultaneously significant effect on customers satisfaction.